Teachers’ personal values, age, and educational setting shape their socialisation values - Tamm, Anni (Journal of beliefs and values, 2020)
Teachers in kindergartens and schools also fill an important role of values educators. The study examined teachers’ socialisation values and their links with teachers’ personal values, age, education, and educational setting (kindergarten vs school). A total of 391 teachers in Estonia filled in the Schwartz’s Portrait Values Questionnaire that assessed their personal and socialisation values. Teachers considered self-transcendence values most important personally and in socialisation of children, followed by openness to change values. At the same time, teachers differentiated between their personal and socialisation values: openness to change was rated higher as a socialisation than as a personal value. The variation in teachers’ socialisation values stemmed from their personal values, teachers’ age, and educational setting.